How do you derive this equation:

y = sin ^ 3 (cosx^3)

Printable View

- Apr 5th 2009, 06:49 PMmathamatics112Trig differentation
How do you derive this equation:

y = sin ^ 3 (cosx^3) - Apr 5th 2009, 07:11 PMmatheagle
This is the chain rule if the cosine is inside the sine, which what this seems to be.

- Apr 5th 2009, 07:16 PMReckoner
- Apr 5th 2009, 07:17 PMmathamatics112
y= sin^3( cos x^3)

= 3 sin ^ 2 ( cos x^3)(coz(cosx^3))(-sinx^3)(3x^2)

= 9 x^2(sin^2)(cos(cos x^3))(-sin x^3))

are my steps right? - Apr 5th 2009, 07:23 PMReckoner
- Apr 5th 2009, 07:27 PMmathamatics112
i'm not seeing it :(

- Apr 5th 2009, 07:33 PMReckoner